If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 3 + -1x = 39x + -10 Reorder the terms: 3 + 4x + -1x = 39x + -10 Combine like terms: 4x + -1x = 3x 3 + 3x = 39x + -10 Reorder the terms: 3 + 3x = -10 + 39x Solving 3 + 3x = -10 + 39x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-39x' to each side of the equation. 3 + 3x + -39x = -10 + 39x + -39x Combine like terms: 3x + -39x = -36x 3 + -36x = -10 + 39x + -39x Combine like terms: 39x + -39x = 0 3 + -36x = -10 + 0 3 + -36x = -10 Add '-3' to each side of the equation. 3 + -3 + -36x = -10 + -3 Combine like terms: 3 + -3 = 0 0 + -36x = -10 + -3 -36x = -10 + -3 Combine like terms: -10 + -3 = -13 -36x = -13 Divide each side by '-36'. x = 0.3611111111 Simplifying x = 0.3611111111
| 1x/10=-2 | | 7x^2-34x-24=0 | | -8+-4+4= | | 114=.5h(10-9) | | 6x+130=11x-5 | | -3y-7=-28 | | 4x+4=4x+24 | | 103-x+2x=6x-7 | | 103-3+2x=6x-7 | | x(x+3x)=8(8+x+2) | | 2x+7x=10x-4 | | Y+2x+10=180 | | 2(n+5)=n+19 | | 5p+2=4-1 | | 7-7q=-15+-9q | | (4y^3-y-1)-(2y^2-3y+7)=0 | | 8y-2=-3(y-3) | | x*x+6x+9=-3x+1 | | 2+12x=123x | | 6-9x=36-13x | | 9st(7s-6t^2)= | | x+6x+9=-3x+1 | | 7(7+6)=x(x+4) | | 180=y+(5x+20) | | -12-15x=33 | | 6(v-9)=-2v-14 | | 9(3n-3)=(4n+8)+2 | | 0.3x+3=-2.3x+0.4 | | 7(x-1)+3(3-x)=5(1-x)-3(2x+1) | | 2(90-x)-6=124 | | 961=400+2x | | 15+5(x-10)=3(x-1) |